6x+3x-3=

Simple and best practice solution for 6x+3x-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3x-3= equation:


Simplifying
6x + 3x + -3 = 0

Reorder the terms:
-3 + 6x + 3x = 0

Combine like terms: 6x + 3x = 9x
-3 + 9x = 0

Solving
-3 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 9x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 9x = 0 + 3
9x = 0 + 3

Combine like terms: 0 + 3 = 3
9x = 3

Divide each side by '9'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= | | 2x=14+2 | | 12-7y=40 | | 12x+y-x+6y= | | 7x-2x+2-x= | | 6n+10=-44 | | 2/3k=4/3 | | 4x^2+176=0 | | 8p-9=49 | | 2x^2+19+24=0 | | 2x/7-2x=x/2+17/2 | | 12/3+4-24/3x8 | | 5+(2-x)/3=7 | | K/4+5=4 | | 4x-9x=45 | | 2.5y-0.25y= | | -4=-1+c/5 | | 8m^2-2m=11 | | 4(2b+6)+11=-8b-13 | | 1/3x^2+4x-3=0 | | 3x-6=2x+2 | | 14j-6+8j-5= | | 3n-2+2n+5= | | 0=3b+27 | | a+2/a-1=a+11/a+4 | | b+12=-21 |

Equations solver categories